Implications of AlphaFold2 for crystallographic phasing by molecular replacement. Issue 1 (23rd December 2021) - McCoy, Airlie J.; Sammito, Massimo D.; Read, Randy J.
Abstract : The implications of the AlphaFold 2 protein structure‐modelling software for crystallographic phasing strategies are discussed. Abstract : The AlphaFold 2 results in the 14th edition of Critical Assessment of Structure Prediction (CASP14) showed that accurate (low root‐mean‐square deviation) in silico models of protein structure domains are on the horizon, whether or not the protein is related to known structures through high‐coverage sequence similarity. As highly accurate models become available, generated by harnessing the power of correlated mutations and deep learning, one of the aspects of structural biology to be impacted will be methods of phasing in crystallography. Here, the data from CASP14 are used to explore the prospects for changes in phasing methods, and in particular to explore the prospects for molecular‐replacement phasing using in silico models.